Contrast Enhanced Three Dimensional Ultrasound for Intraluminal Thrombus Assessment in Abdominal Aortic Aneurysms. (November 2018) - Ghulam, Qasam M.; Bredahl, Kim; Sandholt, Benjamin; Taudorf, Mikkel; Lönn, Lars; Rouet, Laurence; Sillesen, Henrik; Eiberg, Jonas P.
Abstract : Objectives: The impact of intraluminal thrombus (ILT) on abdominal aortic aneurysm (AAA) progression can be investigated non-invasively by three dimensional contrast enhanced ultrasound (3D-CEUS). The aim was to validate 3D-CEUS ILT volume and thickness measurements against computed tomography angiography (CTA), and to determine inter- and intra-operator reproducibility. Methods: The design was for a planned comparison of 3D-CEUS and CTA and of repeated 3D-CEUS measurements in a blinded set up. Consecutive patients with asymptomatic AAA ( n  = 137, maximum diameter 30–55 mm) from a single centre were consecutively assessed by CTA and 3D-CEUS in a blinded setup. After exclusion of failed CTA ( n  = 2) and inconclusive 3D-CEUS ( n  = 8), 127 3D-CEUS/CTA pairs were analysed by Bland–Altman plots. 3D-CEUS inter- and intra-operator reproducibility were determined in a subgroup ( n  = 30) measured twice by two blinded investigators. Results: In 24 of 127 (19%) patients, no ILT was found on 3D-CEUS. Intraluminal thrombus absence was confirmed by 3D-CTA analysis in all but two cases. Mean ILT volume difference between 3D-CEUS and CTA was 2.2 mL (5% of mean volume) and range of variability (ROV) amounted to ± 10.2 mL. Mean ILT thickness difference was 0.6 mm with a ROV of ± 4.6 mm 3D-CEUS inter-operator variations of ILT volume and thickness measurements were low (ROV ± 8.8 mL and ±2.9 mm, respectively). The corresponding intra-operator ROVs were ±7.5 mL and ±3.3 mm, respectively. Conclusions: 3D-CEUS demonstrated good reproducibility and a good agreement with CTA when estimating ILT volume and maximum thickness in AAA patients. It is a promising research tool to investigate potential interactions between ILT, AAA growth, and rupture.